The Right to the Museum: From the White Cube to the Critical Museum - Sara Pastore (Sociologica)
As the museum ecosystem undergoes a process of de- and re-articulation — politically and aesthetically affecting cultural and artistic institutions — museums are increasingly becoming hybrid and transdisciplinary entities. Building on this, the article draws upon institutional critique and critical museology to explore the reconceptualization of the museum as a critical institution: one endowed with social agency and accountability towards the communities that host and engage with it. Focusing on the urban dimension, the article examines the relationship between museums and the premises and practices of critical urbanism, mapping how their interactions with the cities they inhabit have evolved. In doing so, and while intentionally avoiding a developmentalist perspective, the discussion adopts a historical lens — tracing the museum’s trajectory from its industrial emergence through its modernist evolution to its current decolonial and critical reinterpretations. This retrospective provides a foundation to reconsider the museum’s role as an urban actor, proposing a parallel between two key rights: the right to the city and the right to the museum. The argument is further grounded through the analysis of two case studies, which, alongside the theoretical framework, illustrate how museum practices can serve as a means of reengaging with urban experience.